Exploring Self-Disclosure Behavior Among Adolescents in Palembang - Rahmania, Yuliana; Rozzaqyah, Fadhlina; Lubis, Khadijah; Wisma, Nur; Tanjung, Romi Fajar (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2023)
This study aims to describe the self-disclosure of tenth-grade students at SMA Negeri 18 Palembang. This study is descriptive quantitative with a survey design. The sample in this study consisted of 201 students selected using proportional random sampling. The instrument used in this study was a self-disclosure scale with a reliability of 0.852. Data analysis used a quantitative approach with a descriptive method. The results showed that student self-disclosure varied. There were 14 students with very high self-disclosure (7%), 44 students with high self-disclosure (22%), 77 students with moderate self-disclosure (38%), 55 students with low self-disclosure (27%), and 11 students with very low self-disclosure (5%). Based on these research results, it can be understood that the self-disclosure of students in grade X at SMA Negeri 18 Palembang is generally in the moderate category with a mean of 108 and an achievement level of 38%. This study produced a valid and reliable instrument that can be used to collect self-disclosure data, and self-disclosure data can be used as a basis for creating guidance and counseling service programs.